Aspergillus pacemaker lead endocarditis. (April 2013) - Pillai, Jeewan; Mubeen, Mohammad; Chaudhari, Amit; Dalmia, Basant
A 47-year-old man who had a pacemaker implanted 2 years earlier, recently developed a fever and had been on antibiotics for 2 months. He presented with pulmonary emboli, and underwent lead extraction and emboli removal. Histopathology demonstrated Aspergillus. Amphotericin B was continued postoperatively. This rare case of pacemaker lead endocarditis suggests that vigorous medical and surgical intervention can be curative.